Note on a meeting of the Eastbourne Trades Council... [to] discuss a national medical service - British Medical Association; Smyth, J. L.
1943-10-223 1943 1940s 7 pages NOTE ON A MEETING OF THE EASTBOURNE TRADES COUNCIL ON OCTOBER 18TH ON DISCUSS A NATIONAL MEDICAL SERVICE The meeting was attended by Doctors Young, Matthew and Smith who are members of the local branch of the B.M.A. The doctors had previously circulated a questionnaire, copy attached, and Doctor Matthew went through the various points setting out very briefly what he thought was involved in them and the arguments for and against. Dr. Young amplified those points and also stated the case for and against the different items but he seemed to me to be much more biased than Dr. Matthew and he was clearly anxious to guide opinion in favour of B.M.A. policy of extending the health insurance panel system at the present time as an immediate means of dealing with Assumption B of the Beveridge Report. He made a lot of freedom of choice and talked about the danger of doctors being converted into Civil Servants with no initiative, no desire to take responsibility and each one being anxious to pass everything on to somebody else. After the doctors had finished, questions were allowed and several of the delegates present made pointed remarks. One man asked whether the B.M.A. wanted the retention of the system under which, years ago, prescriptions were already made out before the doctors saw the patients and all he had to do was to put the patient's name to it. The doctors said that they wanted a comprehensive medical service free to everybody and that it should include all specialist and other services. At the same time they thought some room should be allowed for private patients so that those who had the money could pay for their own treatment and also they wanted the doctors paid on a capitation basis and not on a salary basis. They asserted that at the present time no preference was given to private patients and that a panel patient could secure anything that was open to a private patient. In reply to a question which I put at that stage, the doctors agreed that panel patients could not get anything under the present scheme beyond the services of the General Practitioner and that if he wanted a specialist, x-rays, hospital, dental, ophthalmic or other services he would have to pay for them as a private patient. I also asked what free choice a person has at present where a doctor sells his practice or where a person goes to hospital. The doctors agreed that the patient had no choice in hospital but said that there he was dealing with specialists and it was not so important to have free choice of specialist as free choice of family doctor. In the case of a practice changing hands, the patients were free, if they so desired, to transfer to another doctor but they admitted that many patients knew nothing of their rights in this direction, that they were not consulted before they were transferred to the new doctor and that in any case, they would not be able to change their doctor unless the doctor to whom they wanted to change agreed to have them. I also asked whether it was not possible to arrange free choice of doctor even in a State Scheme. The doctors agreed that that was so but Dr. Young went on to say that in a State Scheme a doctor would only be allowed to have a certain number of patients and when he had those, others who wanted to be on his panel could not be taken on. He admitted in answer to another question from me that that was exactly what happened at the present time in panel practice and I then had to remind him that he was advocating the continuance of panel practice, and therefore the continuance of the very thing he was condemning in advance as part of a State Scheme. 292/847/2/107